Strategi Pemasaran Pendidikan di MA Al Amiriyyah Blokagung Banyuwangi - Mamlukhah Mamlukhah; Faiz Inayah (Institut Agama Islam Darussalam Blokagung, 2020)
This type of research is qualitative research. Qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation. Qualitative research method is a type of purpose sampling research that is a non-random sampling technique where researchers determine the sampling by determining specific characteristics in accordance with the objectives of the researcher so that it is expected to answer the researcher's problems. So the researchers only need to take important points regarding sampling techniques and user indications. The purpose of this study was to find out how education marketing strategies in MA Al Amiriyyah Blokagung Tegalsari Banyuwangi, efforts in improving education marketing strategies in MA Al Amiriyyah Blokagung Tegalsari Banyuwangi, knowing the driving and inhibiting factors that influence the marketing strategy of MA Al Amiriyyah Blokagung Tegalsari Banyuwangi. Data analysis tools used in this study are interaction models, which consist of data display, data reduction, data collection, conclusion drawing and data verification. The research results obtained are the educational marketing marketing strategy matrix is a strategy of concentration through horizontal integration or stability (there is no change in earnings). With IE matrix (internal external) has an average of 2.50-3.00. With a total IFAS value of 3.00 and an EFAS value of 2.95. The conclusion in this study is the strategy used in education marketing which is divided into two short-term and long-term strategies, efforts to improve education marketing by marketing mix, the driving and inhibiting factors that influence education marketing strategies namely the existence of other educational institutions that are competitors and are the same area, and the feeling of not having a madrasah